2018
DOI: 10.36766/ijag.v2i2.29
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bankruptcy Possibility on Audit Delay and Timeliness (Empirical Study on Manufacturing Companies Listed in Indonesian Stock Exchange in the Period of 2012-2016)

Abstract: Audit delay and timeliness are important factors that influence the quality of accounting information interm of relevance. This study provides empirical evidence to answer the question of how bankruptcypossibility impacts on audit delay and timeliness. This research studies manufacturing firms listed inIndonesian Stock Exchange (IDX) in the period of 2012-2016. Data are taken from official website ofIDX. This study is a quantitative research that seek to find out relationship between independentvariable and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Merdekawati and Arsjah (2011) showed that debt ratio is one of the factors causing companies to be late in submitting their financial reports. Research by Meinarsih et al (2018) on public companies in Indonesia engaged in the manufacturing sector showed that increasing the likelihood of companies going bankrupt will cause audit delays and delays in the publication of financial statements. Nova et al (2019) essentially showed the same result, the greater probability of company failure, the slower submission of financial reports.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Merdekawati and Arsjah (2011) showed that debt ratio is one of the factors causing companies to be late in submitting their financial reports. Research by Meinarsih et al (2018) on public companies in Indonesia engaged in the manufacturing sector showed that increasing the likelihood of companies going bankrupt will cause audit delays and delays in the publication of financial statements. Nova et al (2019) essentially showed the same result, the greater probability of company failure, the slower submission of financial reports.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Pada penelitian (Nugroho et al, 2021) menyatakan bankruptcy prediction mempengaruhi audit delay secara signifikan. Didukung (Meinarsih et al, 2018) pada penelitian yang dilakukan. (Sekar Prabandari, 2021) dalam penelitiannya mengungkapkan tidak terdapat pengaruh bankruptcy prediction terhadap audit delay.…”
Section: Bankruptcy Prediction Terhadap Audit Delayunclassified
“…Hipotesis awal juga menyatakan bahwa bankruptcy prediction mempengaruhi audit delay. Ini sesuai dengan penelitian(Meinarsih et al, 2018) berpendapat ketika sebuah perusahaan mengalami kemungkinan kebangkrutan yang lebih tinggi, hal itu cenderung mempengaruhi auditor untuk menyelesaikan auditnya lebih cepat karena auditor membutuhkan data tambahan yang diperlukan untuk menghasilkan opini yang mengikuti kondisi perusahaan. Pada penelitian yang dilakukan (Sekar Prabandari, 2021) bankruptcy prediction tidak berpengaruh terhadap audit delay.…”
unclassified